Axicabtagene ciloleucel, a first-in-class CAR T cell therapy for aggressive NHL. Issue 8 (3rd August 2018) - Roberts, Zachary J.; Better, Marc; Bot, Adrian; Roberts, Margo R.; Ribas, Antoni
Abstract: The development of clinically functional chimeric antigen receptor (CAR) T cell therapy is the culmination of multiple advances over the last three decades. Axicabtagene ciloleucel (formerly KTE-C19) is an anti-CD19 CAR T cell therapy in development for patients with refractory diffuse large B cell lymphoma (DLBCL), including transformed follicular lymphoma (TFL) and primary mediastinal B cell lymphoma (PMBCL). Axicabtagene ciloleucel is manufactured from patients' own peripheral blood mononuclear cells (PBMC) during which T cells are engineered to express a CAR that redirects them to recognize CD19-expressing cells. Clinical trials have demonstrated the feasibility of manufacturing axicabtagene ciloleucel in a centralized facility for use in multicenter clinical trials and have demonstrated potent antitumor activity in patients with refractory DLBCL. Main acute toxicities are cytokine release syndrome and neurologic events. Axicabtagene ciloleucel holds promise for the treatment of patients with CD19-positive malignancies, including refractory DLBCL.